Perjanjian Pinjam Meminjam Berdasarkan Pasal 1754 KUHperdata - Muhammad Afriza Rifandy; Novita Mayasari Angelia (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Civil Law is a branch of law that regulates relationships between individuals or legal entities of a private nature. Civil Law regulates the rights and obligations of individuals or legal entities in the context of civil relationships, such as agreements, property ownership, legal responsibility, inheritance, marriage, divorce, and contracts. Civil Law usually applies in situations where there is a relationship between individuals or legal entities that stand as equal legal subjects. This is different from Public Law which regulates the relationship between individuals or legal entities and the state or government. Civil Law covers several important areas, including contract law, property law, inheritance law, family law, and labor law. In this area, Civil Law determines the rights and obligations of the parties involved, clarifies legal responsibilities, and provides a legal framework for resolving disputes. The general principles underlying Civil Law include freedom of contract, principles of justice, protection of personal rights, legal responsibility, legal certainty, and compensation for losses incurred as a result of violations or negligence.